BRANISLAV PETRONIJEVIĆ’S LOGIC - Мирко В. Аћимовић (Истраживања, 2012)
The transition from the science of forms of thought and methods of knowledge to thescience of principles of objective logical content of being was indicated through foundations,structure and theoretical scope of formal and metaphysical logic in the philosophical systemof Branislav Petronijević. Hence, the formal logic and metaphysical logic are propedeuticalsciences of Petronijević’s system of metaphysics which together with the theory of knowledgeand logic constitute the pure philosophy in the synthesis of universal knowledge.